The Iban Pantun - Poetry and Song - Patricia Matusky, (Wacana Seni Journal of Arts Discourse, 2004)
Iban oral literature encompasses genres that are chanted or sung whenever they are performed. These genres include entertainment songs, chants (timang or pengap) for high ritual festivals, dirges for the deceased (sabak) and courtship songs (pelandai) for the young at heart. The renong and sugi secular tales are also sung as is the jawang repartee form by a male and a femaJe singer. The poetry called pantun, the legends (ensera), the pelian healing chants and the naku songs to encourage warriors are also genres that are sung in the vast body of Iban oral literature.